2023
DOI: 10.3390/ijms24043742
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of MED12-Associated Coding RNA Transcripts in Uterine Leiomyomas

Abstract: Recent studies have demonstrated that somatic MED12 mutations in exon 2 occur at a frequency of up to 80% and have a functional role in leiomyoma pathogenesis. The objective of this study was to elucidate the expression profile of coding RNA transcripts in leiomyomas, with and without these mutations, and their paired myometrium. Next-generation RNA sequencing (NGS) was used to systematically profile the differentially expressed RNA transcripts from paired leiomyomas (n = 19). The differential analysis indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 112 publications
(127 reference statements)
0
5
0
Order By: Relevance
“…Total RNA was extracted from the xenografts using TRIzol (Thermo Fisher Scientific Inc., Waltham, MA, USA). RNA concentration and integrity were determined using a Nanodrop 2000c spectrophotometer (Thermo Scientific, Wilmington, DE, USA) and an Agilent 2100 Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA) as previously described [ 45 , 46 , 47 ]. Briefly, 2 μg of RNA was reverse-transcribed using random primers for selected genes according to the manufacturer’s guidelines (Applied Biosystems, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted from the xenografts using TRIzol (Thermo Fisher Scientific Inc., Waltham, MA, USA). RNA concentration and integrity were determined using a Nanodrop 2000c spectrophotometer (Thermo Scientific, Wilmington, DE, USA) and an Agilent 2100 Bioanalyzer (Agilent Technologies, Santa Clara, CA, USA) as previously described [ 45 , 46 , 47 ]. Briefly, 2 μg of RNA was reverse-transcribed using random primers for selected genes according to the manufacturer’s guidelines (Applied Biosystems, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…One microgram of total RNA from each tissue was used to produce strand-specific cDNA libraries using the Truseq (Illumina, San Diego, CA, USA) according to manufacturer's instructions. The RNA sequencing was carried out at Novogene Corporation Inc., (Sacramento, CA, USA) and bioinformatics analysis was performed as previously described [19,20]. To visualize the strength of differential gene expression, the Hierarchical clustering and TreeView graph, volcano plot, principal component analysis (PCA) plot, and the Gene Ontology (GO) and KEGG (Kyoto Encyclopedia of Genes and Genomes) Pathway Enrichment Analysis plot were made using Flaski and NcPath [97,98], and the interactive network of lncRNA-miRNA-mRNA was analyzed and made with the ENCORI/starBase (Encyclopedia of RNA Interactomes) and Cytoscape software Version 3.10.1 [37,38,99].…”
Section: Rna Sequencing and Bioinformatic Analysismentioning
confidence: 99%
“…Somatic MED12 mutation in exon 2 occurs at a frequency of 60 to 80% in leiomyomas and has a functional role in their initiation and progression, potentially through its influence on many important pathways, including the Wnt/β-catenin signaling, hedgehog signaling, sex steroid receptor signaling, and transforming growth factor (TGF)-β receptor signaling pathways [12][13][14]17,18]. We have previously reported on the differential expression of protein-coding genes, some of which are influenced by race and MED12 mutation of the tumor [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The CYP450 enzymes perform drug metabolism functions, and their inhibition alters both cellular metabolic and excretory mechanisms in drug candidates, resulting in toxicant bio-accumulation. Six (6) of the dietary phytochemicals are inhibitors of OATP2B1, twenty-nine (29) are inhibitors of OATP1B1, twenty-ve (25) are inhibitors of OATP1B3, ve (5) are inhibitors of MATE1, three (3) are inhibitor of OCT2, nine (9) are inhibitor of BSEP, four (4) are inhibitor of P-GLY, twelve (12) are inhibitor of CYP3A4, thirteen (13) are inhibitor of CYP2C9, nine (9) are inhibitor of CYP2C19, four (4) are inhibitor of CYP2D6, seventeen (17) are inhibitor of CYP1A2. The dietary phytochemicals are non-substrate to P-GLY, but fourteen ( 14) are substrates of CYP3A4, two (2) are substrates of CYP2C9, and only one (1) is CYP2D6 substrate.…”
Section: Pharmacokinetics and Adme/toxicity Pro Lingmentioning
confidence: 99%
“…In addition, the link environmental factors like air pollution, smoking, and alcohol consumption play to this pathogenesis also remains sparingly unclear as to their relationship to mediating the steroids and their receptors and growth factors within the UF signalling pathways [2]. Furthermore, several studies toward understanding some of these signalling factors have shown multiple correlations in UF development with genes dysregulated in leiomyoma versus normal myometrium [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%